Identification of Subterranean Termite Infestation in Residential Areas in Bogor Regency, West Java - Dirna, Fitria Cita; Wahyuningtyas, Irma (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
Identification of Subterranean Termite Infestation in Residential Areas in Bogor Regency, West Java. Subterranean termites are one of the pests that attack buildings. The interaction between termites and buildings significantly affects the durability, safety, and comfort of residential structures. This study aimed to identify the types of termites found in residential environments and determine the intensity of damage and frequency of termite attacks on pine wood (Pinus merkusii). Wood samples cut into 2 cm x 2 cm x 46 cm were conducted using the graveyard test for three months. The identified termite species was Macrotermes gilvus (M. Gilvus). The attack intensity obtained showed that 55% of the wood samples experienced damage due to subterranean termite attacks near the residential building, 30% remained unaffected, and 15% showed damage with penetration ranging from 3% to 75% of the cross-section. These results were reinforced by the high frequency of termite attacks on bait wood, which reached 70% (>40%). These findings are useful for homeowners if the area is later used for building construction. Therefore, preliminary measures are needed to address termite infestations in the area before using it for future building construction.